(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract : Since man created the judiciary as a means of resolving disputes, and striving diligently to surround this means with principles and guarantees that promote and clear it of any suspicion that weaken its confidence or a reason to object or question it, hence many principles that came back as a shield which immunizes the judiciary and protects it from any suspicion or impurity. The principle of judicial security was one of those principles, and perhaps, without exaggeration, we could say that it is one of the most prominent ones, despite the recent appearance of this principle, it came with effects and results that positively affect judges and litigants alike. Since taxes are one of the most important matters that affect the financial position of individuals, the issue of existence of an independent and impartial judiciary is one of the issues that has imposed itself strongly when talking about the extent to which the principle of judicial security can be achieved within the tax judicial environment. On the importance of having a competent judicial body to settle tax disputes, as it is one of the most important guarantees advocated by the aforementioned principle.